DESTRUCTION OF HIMALAYAN MEDICINAL AND AROMATIC PLANTS (HMAPS); A THREAT TO LOCAL LIVELIHOOD IN NEPAL HIMALAYA - POUDEL Shanti, K. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Nepal is a mountainous country situated in the central Himalayas. Medicinal and Aromatic Plants (MAPs) found in Nepal Himalaya is an important sources of livelihood in the mountainous communities in Nepal. However, these resources are not utilized as sustainable source of livelihood in many mountainous communities in Nepal. Previous researchers have argued that collectors’ strong market orientation1 is the main cause of the destruction of biodiversity and loss of the MAPs resources. In addition, based on field research in mountainous communities, this author identifies that low income and low production from other sources, heavy pressure only on few commercially valuable MAPs, lack of local capability and social awareness about the sustainable wild harvesting, and weak local institutions exacerbate destruction of HMAPs, which in turn hurts the livelihood of mountainous communities. Though there are various kind of valuable MAPs available and utilized for their health care need, commercial collection pressure is only on few MAPs; Jatamasee (nardostachys gradndiflora), Katuki (neo-picrorhiza scrophulariifloa hong), Guchichyau (morchella conica) and Atis (aconitum heterophyllum) in a Himalayan district, Humla, Nepal. The field research was conducted in mountainous communities in western Nepal. Methodology included household survey, focus group interview, key informant interview, village meeting and participant observation. The paper analyses the causes of the destruction of HMAPs, contribution of HMAPs in the livelihood of mountainous communities, and some possibilities of sustainable HMAPs utilization in the mountainous communities in Nepal. 1Ghimire S. K et.al (2004). Heterogeneity in Ethnoecological Knowledge and Management of Medicinal Plants in the Himalayas of Nepal: Implication for Conservation. Ecology and Society 9 (3):6 PP. 1-17Acknowledgements: Funded by Nagoya University, GSID, Grant for Overseas Field Research